Die Europäische Währungsunion: Viel reformiert, aber noch nicht am Ziel - Sebastian Dullien (Wirtschaftsdienst, 2016)
Seit Ausbruch der Eurokrise befindet sich die Architektur der Europäischen Währungsunion in einer Dauerreform, die aller Voraussicht nach auch in den nächsten Jahren nicht abgeschlossen sein wird. Trotzdem ist der Euroraum immer noch nicht krisenfest. Besonders die anhaltende Wachstumsschwäche und die weiter mangelnde makroökonomische Koordinierung geben Grund zur Sorge. – – Since the onset of the euro crisis, many aspects of the governance of the euro area have been reformed. Rules for budget control have been tightened, and oversight and resolution of banks has been centralised. Credit facilities have been created for member states who have trouble tapping financial markets. Moreover, the reform process is not over yet but can be expected to continue for another decade before details of a planned fiscal capacity will be implemented. Yet despite all these reforms, the euro area is still not crisis-proof. The permanent low rate of economic growth and the continuing lack of working macroeconomic coordination are particular reasons for concern.
Keywords: E42; F45; 330; Europäisches Währungssystem; Währungsunion